The Effect of Democratic Zoning System on Nigeria Economy: Evidence of Niger State - Musa Abdullahi Sakanko; Joseph David (ETIKONOMI, 2018)
The introduction of the zoning system into Nigeria political space was to aid the smooth rotation of key political positions across the country. This policy is to achieve fairness, peace and equitable distribution of resource. Its adverse effect on the economy is thus something to worry about. Therefore, the study examines the effect of democratic zoning system on the economy of Nigeria, with special reference to Niger state. Employing descriptive statistics and multiple regressions. The results revealed that the elements of democratic zoning vis-à-vis; peace, equity, unity and justice has a positive and significant effect on the growth of the Nigeria economy. The authors thus recommends the government at both levels should focus on providing simultaneous development projects to pave way for peace and unity, zoning system should be incorporated into the Nigeria constitution, unbiased and equitable distribution of resources across the economy.DOI: 10.15408/etk.v17i1.6592